Tinjauan Yuridis Terhadap Tindak Pidana Pembakaran Hutan dan Lahan Oleh Korporasi Dikaitkan dengan Prinsip Strict Liability (Studi Putusan Pengadilan Negeri Tanjung Jabung Timur Nomor : 36/Pid.Sus-LH/2016/PN.Tjt dan Pengadilan Negeri Rokan Hilir Nomor : 393/Pid.Sus-LH/2016/PN.Rhl - Rinta Meinika; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The principle of strict liability is a principle used to impose absolute responsibility on corporationsthat commit crimes under the category of violations. But in practice, it is rare to find cases that imposecriminal liability on corporations because law enforcers have difficulty finding valid evidence.The main problems examined are the criminal acts of forest and land burning by corporationscontained in the decision of the District Court Number: 36 / Pid.Sus-LH / 2016 / PN.Tjt and the decision ofthe District Court Number: 393 / Pid.Sus-LH / 2016 /PN.Rhl.This type of research is a normative legal research comparative type of law. The data sources usedin this study are primary data, secondary data and tertiary data, namely library materials that includeofficial documents, library books, legislation, and other documents relating to research issues.In this study it can be concluded that in the decision Number: 36 / Pid.Sus-LH / 2016 / PN.Tjt thedefendant was declared not proven guilty even though the facts presented in the trial showed that thedefendant committed negligence and had a negative impact on the environment and society. While on theverdict Number: 393 / Pid.Sus-LH / 2016 / PN.Rhl was found guilty and sentenced to a fine of Rp.1,000,000,000 (one billion rupiah) for negligence and negative impact on the environment and society.Authors' advice, firstly, for law enforcement officials in upholding the applicable law does not look at thestatus and level of difficulty in gathering valid evidence, especially in the case of forest and land burning bycorporations, because as is known the principle of strict liability can be used as a guideline for holdingcorporations accountable without requiring an element of proof. Second, for corporate management, inconducting business, especially in the fields related to the environment, they must comply with applicablelegal provisions and should be able to protect the surrounding environment so that no damage to theecosystem and the environment in any form. Third, for the community, it should foster self-awareness thatthe environment in general and the state of the forest in particular must be protected and protected in orderto avoid environmental damage.Keywords: Forest and Land Burning - Corporate Liability - Strict Liability